Revisiting Wańkowicz. The Writer’s Archive - Ziółkowska-Boehm, Aleksandra (Porównania, 2025)
A retrospective article, recalling the publication of archival materials included in the material legacy of Melchior Wańkowicz bequeathed to Aleksandra Ziółkowska-Boehm in the writer’s will; above all, correspondence with his daughter Krystyna, his wife Zofia and Czesław Miłosz. The author cites a number of unknown facts related to the development of these materials for printing and emphasizes in the conclusion that despite the passage of half a century since Wańkowicz’s death, the story of his life still “provides inspiration, mobilizes reflection, forces reflection and evokes curiosity.”